PENERAPAN MEDIA VIRTUAL REALITY UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR NEGERI GADINGAN 02 KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO TAHUN PELAJARAN 2023/2024 - Paraningrum, Widiyaningtyas; Koko Prasetyo; Sri Mulyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Student inactivity occurs due to several factors, this affects student learning outcomes, low student learning outcomes are also influenced by the lack of interesting and interactive learning media, making it difficult for students to understand abstract science concepts. The aim of this research is to determine the increase in activity and science learning outcomes through the application of virtual reality media in class VI students at Gadingan 02 State Elementary School, Mojolaban District, Sukoharjo Regency. The research approach used in this research is Classroom Action Research. The data collection techniques used are observation, tests and documentation. This research was designed using 2 cycles. Activeness in the pre-cycle reached 40.33%, in cycle I reached 77.67%, and in cycle II reached 89.95%. Learning outcomes in the pre-cycle were 3 students who completed with 21.43% learning completeness, in cycle I there were 6 students who completed with 42.85% learning completeness, and in cycle II there were 11 students who completed with 78.57% learning completeness. . Thus, it can be concluded that the application of virtual reality media can increase the active science learning outcomes of class VI students at SD Negeri Gadingan 02, Mojolaban District, Sukoharjo Regency.